A indústria madeireira de São Lourenço do Oeste/SC - Martins, Leonardo (2020)
The present work seeks to understand the origin and development of timber industry in the municipality of São Lourenço do Oeste/SC. This analysis considers the historical process of Brazilian and Santa Catarina industrialization during the 20th century, in addition to analyze of the national, Santa Catarina and lourenciano timber sectors during the period from 2003 to 2010 and from 2011 to 2018, seeking to understand how periods of crises and economic growth impacted the timber sector and in the production of plywood, doors and sawed pine wood, which are the main products produced by the timber companies in São Lourenço do Oeste/SC. During this work, the social-spatial training was considered as analysis category of the western region of Santa Catarina and in the municipality of São Lourenço do Oeste.